The hydrogenosome of Trichomonas vaginalis - Tachezy, Jan; Makki, Abhijith; Hrdý, Ivan (The Journal of eukaryotic microbiology, 2022)
This review is dedicated to the 50th anniversary of the discovery of hydrogenosomes by Miklós Müller and Donald Lindmark, which we will celebrate the following year. It was a long journey from the first observation of enigmatic rows of granules in trichomonads at the end of the 19th century to their first biochemical characterization in 1973. The key experiments by Müller and Lindmark revealed that the isolated granules contain hydrogen-producing hydrogenase, similar to some anaerobic bacteria-a discovery that gave birth to the field of hydrogenosomes. It is also important to acknowledge the parallel work of the team of Apolena Čerkasovová, Jiří Čerkasov, and Jaroslav Kulda, who demonstrated that these granules, similar to mitochondria, produce ATP. However, the evolutionary origin of hydrogenosomes remained enigmatic until the turn of the millennium, when it was finally accepted that hydrogenosomes and mitochondria evolved from a common ancestor. After a historical introduction, the review provides an overview of hydrogenosome biogenesis, hydrogenosomal protein import, and the relationship between the peculiar structure of membrane translocases and its low inner membrane potential due to the lack of respiratory complexes. Next, it summarizes the current state of knowledge on energy metabolism, the oxygen defense system, and iron/sulfur cluster assembly.
Keywords: Trichomonas; Trichomonas vaginalis; mitochondrie; transport proteinů; Protozoan Proteins; protozoální proteiny; Protein Transport; organely; Organelles; hydrogenosome; iron sulfur cluster assembly; Mitochondria; protein import; history; metabolism